Gestalt contexture and contested motives: Understanding video evidence in the murder trial of Officer Michael Slager - Watson, Patrick G (Theoretical criminology, 2023)
This article is situated in ongoing discussions about the influx of images of police violence. To date, much scholarship has centred on Foucauldian notions of knowledge-power and sousveillance. Alternatively, I attend to how video evidence produces understanding of police violence in court through a case study of the murder trial of Officer Michael Slager who shot and killed Walter Scott in North Charleston, South Carolina. While audio and video direct evidence of the moments leading up to Slager's decision to shoot was presented, cross-examination focused more explicitly on post-shooting conduct as circumstantial evidence. This approach highlights an issue for video evidence, that what is to be settled at trial may not be directly re-presented in video. Gurwitsch's notion of Gestalt and Garfinkel's adaptation thereof are proposed as an alternative means of interrogating video evidence.